The Influence of Motivation and Work Experience on Employee Performance at a Logistics Service and Hinterland Development Company - Aulia I, Shafira; Keke, Yulianti; Susanthi, Novi Indah; Veronica, Veronica (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
This study aims to analyze and determine the influence between motivation and work experience on the performance of employees of PT. Multi Terminal Indonesia. This study uses a quantitative method, and the data used is primary data obtained by distributing questionnaires. In addition, this study also uses secondary data obtained from several articles, journals, and similar research. In this study using 78 respondents with a tolerance level of 10% on the Slovin formula, and using a probability sampling technique with a simple random sampling approach. The data analysis technique used in this study is instrument testing with validity and reliability tests, classical assumption tests, and hypothesis testing through the coefficient of determination test, t test, and f test using SPSS 27. The results of this study indicate that there is a significant influence between motivation and work experience variables on the performance of employees of PT. Multi Terminal Indonesia. As well as simultaneously motivation and work experience affect the performance of employees of PT. Multi Terminal Indonesia..